2009
DOI: 10.1111/j.1365-2435.2009.01522.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, ecology and nutritional ecology: toward an integrated framework

Abstract: Summary 1.The science of nutritional ecology spans a wide range of fields, including ecology, nutrition, behaviour, morphology, physiology, life history and evolutionary biology. But does nutritional ecology have a unique theoretical framework and research program and thus qualify as a field of research in its own right? 2. We suggest that the distinctive feature of nutritional ecology is its integrative nature, and that the field would benefit from more attention to formalizing a theoretical and quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
528
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 526 publications
(544 citation statements)
references
References 76 publications
10
528
0
6
Order By: Relevance
“…The ecology of nutrition is a multidisciplinary approach, mainly focusing on living organisms, the environment and the nutritional basis of the cooperation between organisms (function, mechanism, development) and the environment (biotic and abiotic) (Raubenheimer et al, 2009). Considering the great variety of heavy metals in the environment, it is impossible to avoid the presence of heavy metals in the food chain, and in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The ecology of nutrition is a multidisciplinary approach, mainly focusing on living organisms, the environment and the nutritional basis of the cooperation between organisms (function, mechanism, development) and the environment (biotic and abiotic) (Raubenheimer et al, 2009). Considering the great variety of heavy metals in the environment, it is impossible to avoid the presence of heavy metals in the food chain, and in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, even if the body P content is high, consumers can maintain the vitality under low P food if they have abilities to efficiently ingest and assimilate P from the food, and/or to efficiently recycle P acquired within the body for metabolisms as theoretically suggested by Hall (2004) and Loladze et al (2004). Recent studies have shown that food quality for herbivorous consumers in terms of nutritional content is not necessarily optimal in a variety of ecosystems including aquatic and terrestrial habitats (Elser et al 2000a, Fagan and Denno 2004, Raubenheimer et al 2009). This study suggests that although assimilation and metabolic expenditures for multiple elements have received less attention (Kooijman et al 2004, Andersen et al 2007), species-specific traits of these physiological properties should be taken into consideration for clarifying mechanisms determining competitive and exploitative abilities of consumers under qualitatively suboptimal food conditions.…”
Section: Growth Response To Changes In Quantity and Elemental Composimentioning
confidence: 99%
“…Nutritional ecology combines principles of physiology and nutrient availability to predict how a given organism will respond to changes in essential nutrients (Aumann and Emlen, 1965;Raubenheimer et al, 2009). Low nutrient availability relative to the requirement of the organism forces organisms to spend more time acquiring these nutrients or suffer performance deficits (Arms et al, 1974;Sterner and Elser, 2002;Simpson et al, 2006;Geerling and Loewy, 2008).…”
Section: Q1mentioning
confidence: 99%